Guinea Bissau: SOS Info! - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
During the armed conflict of June to August 1998, Guinea Bissau saw the loss of much of its institutional infrastructure, as well as the tragic consequences for the civilian population. The National Centre for Study and Research (INEP), the most...